With Chitosan and PLGA as the Delivery Vehicle, Toxoplasma gondii Oxidoreductase-Based DNA Vaccines Decrease Parasite Burdens in Mice - Yu, Zhengqing; Cao, Wandi; Gao, Xuchen; Aleem, Muhammad Tahir; Liu, Junlong; Luo, Jianxun; Yan, Ruofeng; Xu, Lixin; Song, Xiaokai; Li, Xiangrui (Frontiers in Immunology, 2021)
Toxoplasma gondii (T. gondii) is an intracellular parasitic protozoa that can cause serious public health problems. However, there is no effectively preventive or therapeutic strategy available for human and animals. In the present study, we developed a DNA vaccine encoding T. gondii oxidoreductase from short-chain dehydrogenase/reductase family (TgSDRO-pVAX1), and then entrapped in chitosan and poly lactic-co-glycolic acid (PLGA) to improve the efficacy. When encapsulated in chitosan (TgSDRO-pVAX1/CS nanospheres) and PLGA (TgSDRO-pVAX1/PLGA nanospheres), adequate plasmids were loaded and released stably. Before animals immunizations, the DNA vaccine were transfected into HEK 293-T cells, and examined by western blotting and laser confocal microscopy. Th1/Th2 cellular and humoral immunity were induced in immunized mice, accompanied by modulated secretion of antibodies and cytokines, promoted the maturation and MHC expression of dendritic cells, and enhanced percentages of CD4+ and CD8+ T lymphocytes. Immunization with TgSDRO-pVAX1/CS and TgSDRO-pVAX1/PLGA nanospheres conferred significant immunity with lower parasite burden in mice model of acute toxoplamosis. Furthermore, our results also lent credit to the idea that TgSDRO-pVAX1/CS and TgSDRO-pVAX1/PLGA nanoshperes are substitutes for each other. In general, the current study proposed that TgSDRO-pVAX1 with chitosan or PLGA as the delivery vehicle is a promising vaccine candidate against acute toxoplasmosis.